Thermoelectric Characterization of Quick-Connect Terminals and Conventional Splices Used as Connection Elements in Electrical Installations (Ciencias de la Ingeniería y Aplicadas, 2026)
This study examines the thermal behavior of quick electrical connectors and traditional splices under continuous-load operation in two representative residential circuits: lighting and power. Experimental measurements were conducted over sixty minutes under a constant load, recording the thermal evolution using an infrared camera. The results indicate distinct behaviors among connection technologies in terms of final mean temperature and accumulated thermal rise, with traditional splices reaching the highest values in both circuits. Thermal uniformity across connection points also differed significantly, with compact connectors exhibiting greater homogeneity and traditional splices presenting higher dispersion, suggesting an increased likelihood of hot spots. The comparison between circuits showed higher thermal sensitivity in the lighting system due to its demand level. These findings provide a detailed characterization of the thermal stability of each technology and offer a relevant reference for selecting connection devices in residential electrical installations subjected to continuous operation.
Keywords: Electrical connectors; residential electrical installations; thermal behavior; Joule heating; thermal stability; experimental measurements; electrical safety